Between the objective historical conditions and the construction of another municipal education - Rosilene Lagares; Maria Raimunda Carvalho Araújo de Cerqueira; Robson Vila Nova Lopes; Geraldo Grossi Junior (Universidade Federal do Norte do Tocantins, 2023)
With a historical dialectical materialist perspective and a theoretical-documentary review, the article addresses the understanding of the theoretical-practical conception of the Program for Institutionalization and Management of Municipal Teaching/Education Systems: formation, follow-up, monitoring and evaluation (PRISME), developed in Tocantins with the Municipalities, from August 2022; as well as the discussion about the challenges and possibilities facing the movement of effective institutionalization of the municipal teaching/education systems in the State. From the conception of education understood as a social practice and democratic management, the empirical educational reality of the municipalities is the starting and ending point, being problematized through theoretical and practical instrumentalization in search of transformation. From the analysis of the documents, it is discovered that the objective of PRISME is to ensure continuous training and to constitute a Virtual Environment of an Interactive Educational Character, to accompany, monitor and evaluate the process of institutionalization of the constitutive elements of municipal education. /educational systems and the management of municipal education, with the objective that the Municipalities constitute autonomy and fulfill their educational duties, integrating themselves with the policies and plans of the Union and the State, having as connections the Municipal Education Plan and the Education Articulate The actions as articulators of the system. PRISME presents itself by building the possibilities of overcoming it in the objective historical conditions of the Municipalities.